Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Biologi Siswa - Juwita Juwita; Nuraeni Nuraeni; Munirah Munirah (Journal Innovation In Education, 2024)
This research aims to improve students' Biology learning outcomes by using the Discovery Learning learning model on Virus material in class X.9 UPT SMA Negeri 1 Maros. This research is classroom action research which has been carried out in 2 cycles. The subjects taken in this research were all students in class X.9 UPT SMA Negeri 1 Maros for the 2023/2024 academic year. The data collection technique in this research is (1). Observation, (2). documentation, (3). Test. Based on the research results, it can be concluded that Discovery Learning is effectively used on Virus material. This is shown in cycle I, the average student score was 53.5, and in cycle II it increased to 82.3. Based on the results of observations of the learning model used in the Discovery Learning research, student and teacher activities are at a level that is effective for students.